2015
DOI: 10.1016/j.ydbio.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Wt1 and β-catenin cooperatively regulate diaphragm development in the mouse

Abstract: The developing diaphragm consists of various differentiating cell types, many of which are not well characterized during organogenesis. One important but incompletely understood tissue, the diaphragmatic mesothelium, is distinctively present from early stages of development. Congenital Diaphragmatic Hernia (CDH) occurs in humans when diaphragm tissue is lost during development, resulting in high morbidity and mortality postnatally. We utilized a Wilms Tumor 1 (Wt1) mutant mouse model to investigate the involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 80 publications
1
73
0
Order By: Relevance
“…The normal morphogenetic expansion of the PPFs ahead of muscle (and also nerve and vasculature; Merrell et al, 2015; Sefton et al, 2018), as well as their expansion in the absence of muscle (Merrell et al, 2015) suggested that the PPFs regulate the morphogenesis of the diaphragm’s muscle. Further studies conditionally deleting the CDH-associated genes, Gata4 , WT1 , and β-catenin , in specific embryonic tissues have now definitively shown that mutations in the PPFs (or their associated mesothelium) lead to defective diaphragm development and hernias (Carmona et al, 2016; Merrell et al, 2015; Paris et al, 2015) and so establish that PPFs regulate normal diaphragm development and are a cellular source of CDH. Detailed analysis of Gata4 additionally revealed that the PPFs regulate the proliferation and survival of adjacent muscle progenitors, and because the PPF cells closest to the muscle are PPF-derived MCT fibroblasts, this suggests that these fibroblasts are the critical regulators of the diaphragm’s muscle (Merrell et al, 2015).…”
Section: Diaphragmmentioning
confidence: 97%
“…The normal morphogenetic expansion of the PPFs ahead of muscle (and also nerve and vasculature; Merrell et al, 2015; Sefton et al, 2018), as well as their expansion in the absence of muscle (Merrell et al, 2015) suggested that the PPFs regulate the morphogenesis of the diaphragm’s muscle. Further studies conditionally deleting the CDH-associated genes, Gata4 , WT1 , and β-catenin , in specific embryonic tissues have now definitively shown that mutations in the PPFs (or their associated mesothelium) lead to defective diaphragm development and hernias (Carmona et al, 2016; Merrell et al, 2015; Paris et al, 2015) and so establish that PPFs regulate normal diaphragm development and are a cellular source of CDH. Detailed analysis of Gata4 additionally revealed that the PPFs regulate the proliferation and survival of adjacent muscle progenitors, and because the PPF cells closest to the muscle are PPF-derived MCT fibroblasts, this suggests that these fibroblasts are the critical regulators of the diaphragm’s muscle (Merrell et al, 2015).…”
Section: Diaphragmmentioning
confidence: 97%
“…Brian M Varisco, 1 Lourenco Sbragia, 2,3 Jing Chen, 4 Federico Scorletti, 2,3 Rashika Joshi, 1 Hector R Wong, 1 Rebeca Lopes-Figueira, 2,3 Marc Oria, 2,3 and Jose Peiro 2,3 1 Cincinnati Children′s Hospital Medical Center (CCHMC) Division of Critical Care Medicine; 2 CCHMC Division of Pediatric General and Thoracic Surgery; 3 The Center for Fetal, Cellular, and Molecular Therapy (CCHMC); and 4 CCHMC Division of Biomedical Informatics, Cincinnati, Ohio, United States of America Congenital diaphragmatic hernia (CDH) causes severe pulmonary hypoplasia from herniation of abdominal contents into the thorax. Tracheal occlusion (TO) for human CDH improves survival, but morbidity and mortality remain high, and we do not fully understand the cellular pathways and processes most severely impacted by CDH and TO.…”
Section: Excessive Reversal Of Epidermal Growth Factor Receptor and Ementioning
confidence: 99%
“…While TO for CDH may gain more widespread acceptance in the coming years, there remains an urgent need to understand the cellular responses to CDH and TO so that targeted therapies may be developed to improve fetal lung development and to limit any undesirable effects of TO. There have been reports of how CDH and TO impact lung matrix synthesis (6)(7)(8)(9), lung epithelial function and surfactant (10)(11)(12)(13) and microvascular development (14)(15)(16), and that tracheal occlusion reverses some of resulting in severe pulmonary hypoplasia (2). Despite optimal medical and surgical care, mortality remains high with survivors experiencing severe restrictive lung disease and significant pulmonary hypertension (1).…”
mentioning
confidence: 99%
“…3E). Alteration of the EMT in this area can probably lead to congenital diaphragmatic hernia, a malformation which has been related with Wt1 function (Dingemann et al, 2011;Paris et al, 2015;unpublished results).…”
Section: Contribution Of Coelomic Epithelium-derived Cells To Other Tmentioning
confidence: 99%